THE INFLUENCE OF EXPERTISE AND EXPERIMENTAL PARADIGMS ON THE VISUAL BEHAVIOR OF TENNIS ATHLETES IN RETURNING A SERVE (Kinesiology, 2022)
To return a serve, one must pick up information from the server’s kinematics and anticipate the ball trajectory. Although the perceptual requirements are important, the literature diverges in terms of the differences between experts and novices as well as the importance of the experimental paradigm (in-situ vs. video-based) for the results. This study aimed to address both concerns. We compared experts’ (n=7, 20.6±1.1 years of age) and novices’ (n=7, 20.0±0.4 years of age) visual pattern when returning a serve (Experiment 1) and the influence of the experimental paradigm in experts (Experiment 2). Experts fixated more and longer the upper body and ball, while novices showed a more distributed pattern and with longer fixations outside of the server’s body. Also, the pattern was different when comparing in-situ and laboratory settings, differing mainly in fixation frequency. The influence of expertise was observed in qualitative (relative) and quantitative (absolute) measures of visual behavior with the setting having an important influence. Thus, studies should be as close to the actual situation if trying to understand experts’ behavior.Key words: visual search, gaze behavior, sports, experts, novices